Dynamic Test of Negative Stiffness Damped Outrigger With Damping Amplification - Wang, Meng; Koetaka, Yuji; Sun, Fei‐Fei; Liu, Chao; Nagarajaiah, Satish; Ashida, Yosuke; Du, Xiu‐Li (Earthquake engineering & structural dynamics, 2025)
ABSTRACT This paper proposed a novel negative stiffness damped outrigger with damping amplification (NSDO‐DA) through a smart combination of an L‐shape lever, a precompressed disc spring brace (DSB), and a viscous damper. A theoretical model of the NSDO‐DA considering nonlinear adaptive negative stiffness, damping amplification of nonlinear viscous dampers, and frictions were established. Cyclic tests of disc spring pairs and DSB were presented to verify the feasibility of using DSB as the precompression component of the NSDO‐DA. Subsequently, large‐scale dynamic tests of five different outrigger systems were conducted involving (i) conventional damped outrigger (CDO), (ii) amplified damped outrigger (ADO), (iii) purely negative stiffness mechanism, (iv) negative stiffness damped outrigger (NSDO), and (v) NSDO‐DA. Then, discussions on the dynamic test results and validations of the NSDO‐DA model were provided. The major contributions of this paper are the proposal of the NSDO‐DA and the experimental validation of its two special features: (i) producing negative stiffness force in the parallel direction of the precompression force rather than in the perpendicular direction, making the physical configuration more concise and condensed for outrigger application; (ii) sharing the amplification mechanism of the L‐shape lever for both the viscous damper and the negative stiffness mechanism, leading to an additional damping amplification mechanism for the damper. Moreover, the adaptive stiffness behavior and the frequency‐independent feature of the proposed negative stiffness mechanism were successfully validated by the dynamic tests.